Detection of Very Low-Level Somatic Mosaic COL4A5 Splicing Variant in Asymptomatic Female Using Droplet Digital PCR - Deng, Haiyue; Zhang, Yanqin; Ding, Jie; Wang, Fang (Frontiers in Medicine, 2022)
Background Alport syndrome is a hereditary glomerulopathy featured by haematuria, proteinuria, and progressive renal failure. X-linked Alport syndrome (XLAS) due to COL4A5 disease-causing variants is the most common form. In the case of XLAS resulting from 10–18% presumed de novo COL4A5 disease-causing variants, there are only a few studies for mosaicism in the probands or parents. Very low-level (<1.0%) somatic mosaicism for COL4A5 disease-causing variants has not been published. Materials and Methods Chinese XLAS families with suspected parental mosaicism were enrolled in the present study to evaluate the forms of mosaicism, to offer more appropriate genetic counseling. PCR and direct sequencing were used to detect COL4A5 disease-causing variants harbored by the affected probands in parental multi-tissue DNAs (peripheral blood, urine sediments, saliva, hair), and droplet digital PCR (ddPCR) was used to quantify the mutant COL4A5 allelic fractions in parental different samples such as peripheral blood, saliva, and urine sediments. Results A Chinese asymptomatic female with suspected somatic and germline mosaicism was enrolled in the present study. She gave birth to two boys with XLAS caused by a hemizygous disease-causing variant c. 2245-1G>A in COL4A5 (NM_033380) intron 28, whereas this disease-causing variant was not detected in genomic DNA extracted from peripheral blood leukocytes in the woman using Sanger sequencing. She had multiple normal urine test results, and continuous linear immunofluorescence staining of α2 (IV) and α5 (IV) chains of skin tissue. Sanger sequencing demonstrated that COL4A5 disease-causing variant c. 2245-1G>A was not detected in her genomic DNAs isolated from urine sediments, saliva, and hair roots. Using ddPCR, the wild-type and mutant-type (c.2245-1G>A) COL4A5 was identified in the female's genomic DNAs isolated from peripheral blood, saliva, and urine sediments. The mutant allelic fractions in these tissues were 0.26% (peripheral blood), 0.73% (saliva), and 1.39% (urine), respectively. Conclusions Germline and very low-level somatic mosaicism for a COL4A5 splicing variant was detected in an asymptomatic female, which highlights that parental mosaicism should be excluded when a COL4A5 presumed de novo disease-causing variant is detected.